Characteristics of Vaname Shrimp Farm Residual Water Across Different Shrimp Ages - Supratikno; Enggar Utar; Najmi Firdaus; Lucy Adi Tama (Postgraduate, University of Mataram, 2025)
Vaname shrimp (Litopenaeus vannamei) aquaculture plays a crucial role in the fishery commodities to enhance the economy in Indonesia. The development of Vaname shrimp culture in Bengkunat Coastal Lampung has a strong potential due to its extensive coastline. To support the high demand of vaname shrimp, the intensive shrimp method can address this solution. However, intensive culture has a high distribution of shrimp requires large amounts of feed, that contributes to organic pollution in the water. Therefore, this study aims to determine the characteristics of shrimp farming residual water based on variations in shrimp ages to develop wastewater management strategies. This study was conducted from January 16 to March 12, 2024 at Lumintu shrimp pond in Bengkunat. This research is an exploratory descriptive study with a qualitative approach to assess the total of ammonia, nitrite, total organic matter (TOM), total bacterial abundance (TBC), and total vibrio bacteria (TVC). In conclusion, the study indicates that ammonia, nitrite, total bacterial count (TBC), and total Vibrio count (TVC) are within acceptable ranges. However, total organic matter (TOM) surpasses safe levels for shrimp ponds.